PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MARK DYNAMICS INDONESIA MEDAN - Nababan, Tiorika; Sitorus, Syahrial; barus, Apriwati br (JEBIM Prima, 2024)
In the research conducted at PT. Mark Dynamics Indonesia Medan, the primary focus was to investigate the impact of organizational culture and job satisfaction on employee performance. The company, a foreign investment entity engaged in manufacturing ceramic gloves (hand former manufacturer), faced challenges related to the lack of organizational culture, particularly in terms of company values. The identified problem was reflected in employee turnover, indicating potential issues with job satisfaction. The research aimed to answer the formulated problem: